(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2023)
The purpose of this study was to find out the implementation of the public policy of accepting new online students at SMAN 3 Bulukumba. This study used qualitative descriptive research. The results of this study showed that the implementation of the online new student admissions public policy (PPDB) at SMA Negeri 3 Bulukumba was going quite well. The communication was g⁴, both in terms of transmission and in terms of clarity. The resources were quite adequate, both human resources, facility resources and budget resources. The disposition of the implementer was also good, committed, professional and honest, the bureaucratic structure was also good, not complicated and had clear Standar Operasional Prosedur.